Cancer Immunology 2014
DOI: 10.1007/978-3-662-44006-3_9
|View full text |Cite
|
Sign up to set email alerts
|

The CD95/CD95L Signaling Pathway: A Role in Carcinogenesis

Abstract: Apoptosis is a fundamental process that contributes to tissue homeostasis, immune responses, and development. The receptor CD95, also called Fas, is a member of the tumor necrosis factor receptor (TNF-R) superfamily. Its cognate ligand, CD95L, is implicated in immune homeostasis and immune surveillance, and various lineages of malignant cells exhibit loss-offunction mutations in this pathway; therefore, CD95 was initially classified as a tumor suppressor gene. However, more recent data indicate that in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 173 publications
0
10
0
Order By: Relevance
“…The rationale for this treatment was found in experimental data that indicated that IVIgs are capable of preventing and treating bleomycin-induced pulmonary fibrosis in mice through the reduced expression of collagen-I protein in the affected lungs [23, 24]. Postulated mechanisms of this anti-fibrotic action of IVIg include modulation of cytokine production, inhibition of the complement reaction and inhibition of the CD95 receptor (Fas) activity through the presence of anti-Fas antibodies in IVIg [23, 54, 55]. Subsequently, one dose of cyclophosphamide, a nitrogen mustard alkylating and lymphocyte-modulating agent, was administered.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for this treatment was found in experimental data that indicated that IVIgs are capable of preventing and treating bleomycin-induced pulmonary fibrosis in mice through the reduced expression of collagen-I protein in the affected lungs [23, 24]. Postulated mechanisms of this anti-fibrotic action of IVIg include modulation of cytokine production, inhibition of the complement reaction and inhibition of the CD95 receptor (Fas) activity through the presence of anti-Fas antibodies in IVIg [23, 54, 55]. Subsequently, one dose of cyclophosphamide, a nitrogen mustard alkylating and lymphocyte-modulating agent, was administered.…”
Section: Discussionmentioning
confidence: 99%
“…However, FasL can be a potent pro‐tumorigenic inflammatory factor, inflammatory cells, Being attracted by stimulating the release and expression of inflammatory cytokines and chemokines. There is also evidence that Fas induce proliferation, invasion and cell survival (Fouqué, Debure, & Legembre, ). Therefore, Fas can have two completely opposite effects in CRC, suppressor, or stimulator of tumor growth and metastasis.…”
Section: Death Receptor Signaling Pathwaymentioning
confidence: 99%
“…When it comes to DRs, Fas/CD95 (also called APO-1) is considered to be the prototypic and major member of the death-receptor family, a subgroup of the TNFRSF, which also includes the TRAIL receptors TRAIL-R1 (a.k.a., DR4) and TRAIL-R2 (a.k.a., DR5) and can transmit apoptotic signals through the presence of a cytoplasmic DD [46,47]. The interaction of Fas/CD95 with its cognate ligand (FasL/CD95L) results in the following: 1) receptor oligomerization and aggregation; 2) recruitment of the adaptor protein FADD, through homotypic interaction between the DDs of both Fas/CD95 and FADD; and 3) subsequent binding of procaspase-8 or -10 to FADD through their respective DEDs that eventually leads to caspase-8/10 activation [48].…”
Section: Fas/cd95-mediated Apoptosismentioning
confidence: 99%
“…1) have been reported [89,90], with most of the mutations distributed within the Fas/CD95 DD [47,89]. Fas/CD95 mutations have only been detected in a minor percentage of MM patients, all of them located at the DD of the DR, and therefore, it is not a widespread feature but might contribute to the pathogenesis and progression of myeloma in some patients [91,92].…”
Section: Fas/cd95 In the Regulation Of Apoptosis In Hematologic Cellsmentioning
confidence: 99%
See 1 more Smart Citation